Ease of Use and Usefulness of Medication Reminder Apps among Rural Aging Adults. Issue 3 (3rd July 2019) - Shade, Marcia; Boron, Julie; Manley, Natalie; Kupzyk, Kevin; Pullen, Carol
ABSTRACT: Older adults manage multiple medications for chronic disease and those living in rural areas are impacted by health care disparities due to health provider shortages and fewer pharmacies. The use of downloadable medication reminder apps on smartphones may serve as a strategy for medication self-management of chronic diseases. In this feasibility study, thirteen rural older adult participants downloaded Medisafe® and used the app to manage their daily medications. The community-dwelling aging adults in this pilot perceived the Medisafe® as not difficult to use, useful for medication tracking and providing reminders for the self-management of multiple medications.